The Influence of Problem Based Learning Models on Students' Learning Motivation in Learning Civics Class III SDN 060868 Medan - Aulia Sahdia (Berpusi Publishing, 2025)
The purpose of this study was to determine the learning motivation of students in the subject of PPKn class III SDN 060868 Medan in the control and experimental classes and to determine the effect of the Problem Based Learning learning model on student learning motivation in the subject of PPKn class III SDN 060868 Medan. This study was conducted at SDN 060868 in class III A as a control class with 26 students and class III B as an experimental class with 23 students with a total of 49 students. The research method uses a quantitative approach. The sampling technique used in this study is purposive sampling, a sample determination technique with certain considerations. This research instrument uses an observation sheet and data analysis techniques are carried out with normality tests, homogeneity tests and hypothesis tests using independent sample t-tests. The results of the study obtained by the control class pretest before using the conventional learning model with an overall average value of 53. The experimental class pretest before using the Problem Based Learning learning model with an overall average value of 50. And in the post test of the experimental class after using the Problem Based Learning model with an overall average value of 91. A significance value of 0.000 was obtained, which means there is a difference or influence of student learning motivation in PPKn learning using the Problem Based Learning learning model. It can be concluded that Ha is accepted and H0 is rejected, there is an influence of the use of the Problem Based Learning learning model on learning motivation in PPKn lessons on the material of rights and obligations of class III SDN 060868 Medan.